Dose-modified lenalidomide induces sustained hematological response in patients with intermediate to high risk myelodysplasia - Alhossain A. Khalafallah; Bernadene Fernandopulle; Terry Brain (Mediterranean Journal of Hematology and Infectious Diseases)
No Abstract Available